Purpose-oriented review of public health surveillance systems: use of surveillance systems and recent advances - Mowafa Househ; Hurmat Ali Shah (BMJ Public Health)
Public health surveillance systems are an important tool for disease distribution and burden of disease as well as enable efficient distribution of resources to fight a disease. The surveillance systems are used to detect, report, track a disease as well as assess the response to the disease and people’s attitudes. This paper provides a framework of review for purpose-oriented categorisation of public health surveillance systems. The framework for review of surveillance systems divides the systems into distribution or monitoring or prediction oriented. While there can be other categorisation based on data sources and data types used, the framework for review in this paper provides a cohesive system which can engulf such categories. The framework of review in this paper is purpose oriented, which categorises the surveillance system according to their stated objectives, which are the most important aspect of any public health surveillance system. This review and the framework of categorisation provide comprehensive details of the surveillance systems in terms of data types used, source of data and purpose of the surveillance system.